INVESTING THE CANVAS MODEL BUSINESS DEVELOPMENT STRATEGY AND EMPLOYEES' UNDERSTANDING OF THE FISHERIES INDUSTRY COMPANY STRATEGY (Case study on CV. Manage Anugerah Bahari Semarang) - Fazlur Rahman Aziz; Mirwan Surya Perdhana (Jurnal Akuntansi dan Pajak, 2023)
CV Manage Anugerah Bahari is a company engaged in fisheries. Companies that grow and develop need the right business model to achieve the company's vision and mission. One business model that has succeeded in turning a complex business model into a simple and easy to understand business model is the Business Model Canvas developed by Alexander Osterwalder and Yves Pigneur. The nine elements used in this research include the value proposition, customer segments, channels, customer relationships, kay activities, key resources, key partnerships, cost structure, and revenue streams. The purpose of this study is to analyze the company's business model CV Manajemen Anugerah Bahari through a business model canvas approach, identify the key factors that are strengths and weaknesses that affect the company's operations CV Manajemen Anugerah Bahari, formulate a strategic plan needed for company development. The results of the business model canvas show that the company needs to improve its business model and strategy for the future development of the CV Manage Anugerah Bahari company, expand marketing, form a marketing team for door to door sales promotions, and train employees on a regular basis to optimize employee functions. The type of research used in this research is descriptive qualitative research. While the data collection techniques used are interviews and focus group discussions. Keywords: business model, BMC, business strategy, fishing industry